Recent advances on microalgae cultivation for simultaneous biomass production and removal of wastewater pollutants to achieve circular economy. (November 2022) - Wan Mahari, Wan Adibah; Wan Razali, Wan Aizuddin; Manan, Hidayah; Hersi, Mursal Abdulkadir; Ishak, Sairatul Dahlianis; Cheah, Wee; Chan, Derek Juinn Chieh; Sonne, Christian; Show, Pau Loke; Lam, Su Shiung
Graphical abstract: Highlights: Emerging microalgae cultivation technologies are reviewed. Value-added compounds in microalgae and its role in sequestering CO2 are reviewed. Microbubbles technology can enhance microalgae mixing and CO2 fixation rate. Role of microalgae as phycoremediation agent in treating wastewater is discussed. Circular economy of sustainable microalgae biorefinery is discussed. Abstract: Microalgae are known for containing high value compounds and its significant role in sequestering carbon dioxide. This review mainly focuses on the emerging microalgae cultivation technologies such as nanomaterials technology that can improve light distribution during microalgae cultivation, attached cultivation and co-cultivation approaches that can improve growth and proliferation of algal cells, biomass yield and lipid accumulation in microalgal. This review includes a comprehensive discussion on the use of microbubbles technology to enhance aerated bubble capacity in photobioreactor to improve microalgal growth. This is followed by discussion on the role of microalgae as phycoremediation agent in removal of contaminants from wastewater, leading to better water quality and high productivity of shellfish. The review also includes techno-economic assessment of microalgae biorefinery technology, which is useful for scaling up the microalgal biofuel production system or integrated microalgae-shellfish cultivation system to support circular economy.